Deformed gap space using macro‐micro FEA model and transferred into a CFD model. Issue 1 (25th October 2016) - Anwar, Ali; Gorash, Yevgen; Dempster, William; Nash, David
Abstract: Using a cylindrical nozzle and seat of a Pressure Relief Valve (PRV) the surface form and waviness is modelled using actual metrological data i. e. average surface form and waviness ( W a and W sm ) in a1 4 symmetry manner. To model the surface waviness the technique used is based on the summing technique created by Tsukizoe & Hisakado [1, 2] for micro contact analysis. Due to the actual surface form measurements being in the micro‐meter range, the model is required to incorporate micro and macro‐meter dimensions. The material in question is stainless steel. The deformed finite element analysis model is then transferred into a CAD geometry allowing the void space to be meshed and solved using computational fluid dynamics. © 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)